High density lipoprotein 3 inhibits oxidized low density lipoprotein-induced apoptosis via promoting cholesterol efflux in RAW264.7 cells - Jiang Pei; Yan Peng-ke; Chen Jian-xiong; Zhu Bing-yang; Lei Xiao-yong; Yin Wei-dong; Liao Duan-fang (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the protective effect of high density lipoprotein 3 (HDL3) on oxidized low density lipoprotein (ox-LDL)-induced apoptosis in RAW264.7 cells. Methods: RAW264.7 cells were exposed to 50 mg/L ox-LDL for various durations up to 48 h, and apoptosis was detected using Hoechst 33258 staining and flow cytometric analysis. Total cholesterol levels were detected by high performance liquid chromatography, cholesterol efflux was determined by Tritium labeling, and the cellular lipid droplets were assayed by oil red O staining. Results: Treatment with 50 mg/L ox-LDL for 12, 24, and 48 h increased the apoptotic rate of RAW264. 7 cells in a time-dependent manner. The peak apoptotic rate (47.7%) was observed after 48 h incubation. HDL3 at various concentrations (50 mg/L, 100 mg/L, and 200 mg/L) inhibited the ox-LDL (50 mg/L for 48 h)-mediated apoptosis that was accompanied by an increased rate of intracellular cholesterol efflux, and decreased total cholesterol levels in cells in a concentration-dependent manner. Blockage of cholesterol efflux by brefeldin decreased the protective effect of HDL3 on ox-LDLinduced apoptosis. Increase of the cholesterol efflux effected by another cholesterol acceptor, β-cyclodextrin, led to a dramatic decrease in the apoptotic rate of cells. Conclusion: HDL3 antagonizes ox-LDL-induced apoptosis in RAW264.7 cells, through reducing the accumulation of toxic cholesterol.